Viscous Poisson's ratio, bulk and shear viscosity during electrical field assisted sintering of polycrystalline ceria - Cao, Chen; Mücke, Robert; Wakai, Fumihiro; Guillon, Olivier (Scripta materialia, 2020)
Uniaxial viscous Poisson's ratio, bulk and shear viscosities were measured by discontinuous sinter-forging without and with alternating current electric fields under the same conditions, i.e. by keeping the sample temperature constant. This precaution enables the exclusion of any macroscopic Joule heating. Major findings are: (i) viscous Poisson's ratio increases with the relative density, with and without electric field; (ii) viscous Poisson's ratio increases with the presence of electrical fields; (iii) changes in the viscous Poisson's ratio can be correlated to a clear decrease in shear viscosity, which can be attributed to an easier grain boundary sliding under electric field. [Display omitted]